-5.7(4t+6)-2.3(3t-5)=

Simple and best practice solution for -5.7(4t+6)-2.3(3t-5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5.7(4t+6)-2.3(3t-5)= equation:


Simplifying
-5.7(4t + 6) + -2.3(3t + -5) = 0

Reorder the terms:
-5.7(6 + 4t) + -2.3(3t + -5) = 0
(6 * -5.7 + 4t * -5.7) + -2.3(3t + -5) = 0
(-34.2 + -22.8t) + -2.3(3t + -5) = 0

Reorder the terms:
-34.2 + -22.8t + -2.3(-5 + 3t) = 0
-34.2 + -22.8t + (-5 * -2.3 + 3t * -2.3) = 0
-34.2 + -22.8t + (11.5 + -6.9t) = 0

Reorder the terms:
-34.2 + 11.5 + -22.8t + -6.9t = 0

Combine like terms: -34.2 + 11.5 = -22.7
-22.7 + -22.8t + -6.9t = 0

Combine like terms: -22.8t + -6.9t = -29.7t
-22.7 + -29.7t = 0

Solving
-22.7 + -29.7t = 0

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '22.7' to each side of the equation.
-22.7 + 22.7 + -29.7t = 0 + 22.7

Combine like terms: -22.7 + 22.7 = 0.0
0.0 + -29.7t = 0 + 22.7
-29.7t = 0 + 22.7

Combine like terms: 0 + 22.7 = 22.7
-29.7t = 22.7

Divide each side by '-29.7'.
t = -0.7643097643

Simplifying
t = -0.7643097643

See similar equations:

| v(2)=1600 | | 6-6b=b-2(1+3b) | | v=1600 | | 6-6b=n-2(1+3b) | | 50-3+2/3=50 | | (2y)(7x^2)(2y^7x^8)= | | 7n-(3n-5)=21 | | 8x+3(x+2)=6+7x | | 15=3(7y-2) | | 3(7x-7)=9 | | 37=-3+5(x+7) | | 5a-15=2+2(2+6a) | | 3(a+4)=7a | | 0.7p+0.3=3.1 | | p(t+1)=-2 | | 3x+2=210 | | 8+16x+19=17x-9-5x | | 3-2(3x-6)=8 | | 4n+38=-6(n-8) | | 3y^2+9y-9=0 | | -6m-4(1-8m)=26-4m | | .67x+4=2x | | 5(4x+7)+7x=-2x+35 | | s/12-3=5 | | -8b+38=-2(7b-7) | | 2.7x+2+12x+1=2 | | 5xy-13xy= | | 21-(x+6)=4x-5 | | -13b-17-5b=2b-10-20b-7 | | -8(-2-5x)=6x-18 | | 7(x-8)+27=2(x-7) | | x+8a=43+ax-5a |

Equations solver categories